Volcanoes And Earthquakes With Foldout Volcanic Scene - Don Harper, Studio Boni/Galante (Illustrator), Lorenzo Cecchi (Illustrator)
Part of a series of books, which cover a wide range of subjects, this book provides information about the structure of the Earth, why and how volcanoes and earthquakes occur, where they are most likely to occur and what effects they have. Some accounts of famous volcanoes and earthquakes are given. The book features a gatefold which tells the story of Mount Vesuvius's sudden and catastrophic eruption over Pompeii. In addition, there is a fun quiz enabling children to text their knowledge.